Performance and carcass characteristics of Santa Inês lambs fed protein diets - Silva,Janaina L. (2015)
The objective of this study was to determine the best level and the effect of diets containing different levels of crude protein (CP) on performance and carcass characteristics of feedlot Santa Inês lambs. In trial 1, eight intact lambs with an average live weight of 25.8 kg were distributed in two 4 x 4 Latin squares and were kept in individual metabolic cages. The total collection of feces was used to estimate digestibility and the total urine collection was used to determine the nitrogen balance. In trial 2, 32 intact lambs with an average live weight of 22.0 kg were distributed in an completely randomized design with eight repetitions and were kept in individual metabolic cages. For both trials, the diets consisted of four levels of CP (14.25; 15.50; 16.75; and 18.0%), with 40% corn silage and 60% concentrate in the dry matter. The increase in crude protein levels in the diets did not alter the digestibility, performance, or carcass characteristics of feedlot-finished Santa Inês lambs; therefore, a level of 14.25% crude protein is recommended, as it allowed for satisfactory gains in animal performance.